Social relevance of science and technology produced by science councils in South Africa: the case of the CSIR - Nkhumise, Lesego Lucretia (My University, 2015)
Science councils in South Africa have a mandate to produce R&D that contributes to the improvement of the quality of life of the South African population through science and technology (S&T). However, science councils seem to respond to the demands of the funders at the expense of user needs and priorities. The purpose of this study is to explore the extent to which S&T produced by science councils is relevant to social needs of users. Using the case study approach, the case of the CSIR Built Environment (BE) operating unit was selected for the study, with a specific focus on water provision projects. Data were collected from users of technology (individuals and focus groups), stakeholders in the communities, as well as the CSIR as an organisation. The study explores the implications of better integration of social dimensions into the study and practice of S&T. It is the researcher’s view that what is needed is a conscious and determined reorientation of science, technology and innovation to tackle these societal problems. The study, by focusing on social relevance makes a case that there is a need for greater attention on the political and even ideological content of S&T production activities and the interactions of science councils with users. This should include issues of power, control and ownership of resources, as well as governance of the S&T production process. Science councils are likely to improve the social relevance of the S&T they produce by increasing the consideration of the context and its implications when developing science and technology. Science councils are also likely to close the gap between the technology and the users. Participatory approaches to development are recognized as inherently superior to technocratic ones. A case is made for user involvement in determining and shaping S&T in line with the participatory development approach which advocates that S&T must address the priorities of user needs in order to be socially relevant. The social relevance of S&T produced by science councils in South Africa based on the case of the CSIR BE unit water management project can be improved. Overall, there was an opportunity for the CSIR to improve the relevance of the S&T it produces by being more effective in managing its interactions with users and stakeholders.
Thesis (M.M. (Innovation Studies))--University of the Witwatersrand, Faculty of Commerce, Law and management, Graduate School of Business Administration, 2014.